NUTRITION FEATURES OF MEDICAL STUDENTS - Yuldasheva Ch.T (Western European Studies, 2025)
The problem of health protection and prevention of diseases, the development of which is partially or completely related to nutrition, remains quite relevant. The student life is very rich, diverse, and characterized by a great toll on all functional systems of the body. The analysis of the student diet through a questionnaire shows that their diet is irrational due to the violation of the quantitative and qualitative characteristics. The diet of the students involved in the study is unvaried, lacking in vegetables, fruits, dairy products, meat, and tends to skew towards excessive consumption of fast food. Most of the respondents have dyspeptic disorders. At the same time, a third of the respondents have a digestive system pathology. The results obtained are useful for solving the problem of student diet.
Keywords: students; dietary regime